2023
DOI: 10.1007/s10637-023-01328-9
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics, Pharmacogenomics, and Adverse Events of Osimertinib and its Two Active Metabolites, AZ5104 and AZ7550, in Japanese Patients with Advanced Non-small Cell Lung Cancer: a Prospective Observational Study

Abstract: Background: Potential novel strategies for adverse event (AE) management of osimertinib therapy, including therapeutic drug monitoring and the use of biomarkers, have not yet been fully investigated. This study aimed to evaluate (1) the relationship between exposure to osimertinib, especially its active metabolites (AZ5104 and AZ7550), and AEs, and (2) the relationship between germline polymorphisms and AEs. Methods: We conducted a prospective, longitudinal observational study of 53 patients with advanced non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 36 publications
4
13
0
Order By: Relevance
“…The simulations conducted in this study strongly demonstrated that albumin level has a substantial impact on the PK variables of OSI as well as EGFRm + inhibition. These findings align well with multiple clinical observations where albumin levels in patients have shown a strong correlation with clinical efficacy ( Brown et al, 2017 ; Yokota et al, 2022 ; Ishikawa et al, 2023 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The simulations conducted in this study strongly demonstrated that albumin level has a substantial impact on the PK variables of OSI as well as EGFRm + inhibition. These findings align well with multiple clinical observations where albumin levels in patients have shown a strong correlation with clinical efficacy ( Brown et al, 2017 ; Yokota et al, 2022 ; Ishikawa et al, 2023 ).…”
Section: Discussionsupporting
confidence: 90%
“…Variations in f up can result in greater PK variability. Moreover, several clinical studies have demonstrated that the level of plasma albumin, which predominantly binds to OSI ( Food and Drug Administration FDA, 2015 ), can influence the distribution and clearance of OSI in NSCLC patients, and have a statistically significant correlation with the efficacy of OSI in NSCLC patients ( Yokota et al, 2022 ; Ishikawa et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the PBPK models of gefitinib and osimertinib were built using the same equations. Nonetheless, a particularity of osimertinib is that one of its metabolites, AZ5104, also acts as an EGFR-TKI [ 11 ]. The metabolization of osimertinib to AZ5104 in the liver has therefore been modeled, as well as the equations of distribution of AZ5104 from the liver to different tissues and tumors.…”
Section: Methodsmentioning
confidence: 99%
“…While ABCB1 CL int,u and EGFR T 0 did not exhibit a signi cant impact EO trough in the sensitivity analysis, further research was still made to evaluate the effect of these modeling parameters on EO trough in BRT. This decision was in uenced by the signi cant impact of ABCB1 activity on OSI exposure observed in clinical studies [14,15] , as well as the association EGFR expression with worse progression in patients [48] .…”
Section: Sensitivity Analysis Of Modelling Parametersmentioning
confidence: 99%